The Manifesto of Human Rights and the Covenant of the Prophet and the Khilafah Rashidah: A comparative study - Dr Ashfaq Ahmed; Dr. Muhammad Abdus Salam Sabir (jihat-ul-islam, 2024)
Islam is the first conveyor of human rights. The Qur’an and the autobiography of the Holy Prophet (peace and blessings of Allah be upon him) are the foundations of human rights. The Holy Prophet (peace and blessings of Allah be upon him) gave teachings related to human rights on various occasions and showed kindness to human beings and gave people their original rights which humanity was deprived of for a long time. These rights cover all aspects of human life and all classes of people. Even after the departure of the Holy Prophet, when the Rashidah Caliphate began, the process of protecting and respecting human rights continued with full dignity. The Universal Declaration of Human Rights (UDHR) which is being discussed now a days, all the rights related to the individual are the counterfeits of the rights granted by Islam fourteen hundred years ago. The United Nations has not introduced any additional human rights in its UDHR. One of the objectives of the United Nations is the establishment and protection of fundamental human rights without discrimination.